2015
DOI: 10.1891/0886-6708.vv-d-13-00075
|View full text |Cite
|
Sign up to set email alerts
|

Health Implications of Partner Violence Against Women in Ghana

Abstract: This article explores the health implications of partner violence against women in Ghana using data from northern Ghana. Face-to-face structured interviews were conducted with a sample of 443 women contacted at health facilities in the northern region. Results indicate that 7 out of 10 women have experienced intimate partner violence (IPV) within the past 12 months; 62% had experienced psychological violence, 29% had experienced physical violence, and 34% had experienced sexual violence. Participants reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 39 publications
2
28
1
Order By: Relevance
“…In line with previous research findings (Issahaku, 2015;Hahm et al, 2017;Honda et al, 2018;Pengpid et al, 2018), these women who had experienced abusive relationships reported physical pain, a low level of self-esteem and self-worth, depression and trauma-related symptoms. A sense of disempowerment occurred in particular when they felt that there was nobody to help them and they had nowhere to go.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In line with previous research findings (Issahaku, 2015;Hahm et al, 2017;Honda et al, 2018;Pengpid et al, 2018), these women who had experienced abusive relationships reported physical pain, a low level of self-esteem and self-worth, depression and trauma-related symptoms. A sense of disempowerment occurred in particular when they felt that there was nobody to help them and they had nowhere to go.…”
Section: Discussionsupporting
confidence: 91%
“…Intimate partner sexual violence (IPSV) is grave in nature, and it can cause several mental and/or physical health problems or disabilities. Researchers have found that women who have experienced sexual violence by a partner might suffer from PTSD (Bennice et al, 2003;Kessler et al, 2017;Zakrison et al, 2017;Honda et al, 2018), depression (Davhana-Maselesele et al, 2014;Honda et al, 2018), anxiety (Jaquier et al, 2015;Honda et al, 2018), substance and alcohol abuse (Decker et al, 2014;Jaquier et al, 2015;Hahm et al, 2017;Pengpid et al, 2018), somatic symptoms (Honda et al, 2018), sleep problems (Issahaku, 2015), and suicidal ideation and/or attempt (Sedziafa et al, 2016;Honda et al, 2018;Pengpid et al, 2018). They might also experience an unwanted pregnancy, abortion, being infected with HIV, and experience other forms of physical issues such as facial injuries, physical weakness, hypertension, and genital problems (Sedziafa et al, 2016).…”
Section: " I Had To Do That [What They Saw On Porn Clip] … I Didn't Hmentioning
confidence: 99%
“…Women suffer different levels of intimate partner violence, including some with multiple injuries, repeated injuries, and requiring medical attention. These injuries are visible and easier to study; however, the psychological harm caused by stress reaction is not so easily understood 3 . Researchers have shown correlations between HIV and IPV in both -industrialized and African Journal of Reproductive Health December 2017; 21 (4): 46 developing‖ nations 4 .…”
Section: Introductionmentioning
confidence: 99%
“…Studies by other authors have found similar results (Machisa et al, 2018;Sabri et al, 2019;Eric Y. Tenkorang, Owusu, Yeboah, & Bannerman, 2013) as factors that led to intimate partner violence. In most cultures, men control and dominate their partners in Ghana (Dickson et al, 2020;Issahaku, 2015;Owusu-Addo et al, 2018;E. Y. Tenkorang, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Even though there is literature about the perpetration of IPV in Sub-Saharan Africa and Ghana (Addo-Lartey et al, 2019;Adomako & Darkwa Baffour, 2019;Amegbor, Yankey, Rosenberg, & Sabel, 2020;Apatinga & Tenkorang, 2020;Baffoe-Whyte & Sossou, 2019;Cofie, 2018;Dako-Gyeke et al, 2019;Dery, 2019;Dickson et al, 2020;Doat, Negarandeh, & Hasanpour, 2019;Issahaku, 2015;Owusu-Addo et al, 2018;E. Y. Tenkorang, 2019), no single study has been done with the factors that led to male partners' perpetration of violence against their female HIV positive partners.…”
Section: The Theoretical Basis Of Intimate Partner Violence Perpetrationmentioning
confidence: 99%